The Direct Dependence of SCADA Systems on Communications Infrastructure and Electric Power Supply. (2015) - Damian, Claudiu; Tirnovan, Radu Adrian; Hotea, Alexandru; Sava, Sorin
Abstract: Electrical distribution grid and the data transmission networks used by SCADA systems have a great impact on daily life, their proper functioning is essential to modern society. There are generally dependent (bi) directional and reciprocal relationships between the two networks, so that they are mutually dependent. Dependence is particularly true because in situations of failure in the power system, information and communication technology must be used and largely is necessary to have a trust between the two systems so that the two systems become even more dependent. Successful operation of any service that is part of the data transmission networks used by SCADA systems, depends heavily on the operating state of the power system. Malfunction of data transmission system might lead to cascading defects in its infrastructure. Research programs emphasize the practical and methodological great difficulties of dependence of the two systems. Interactions that occur between hardware systems, software and human operators that are part of the two systems, highlight the difficulty of modeling programs to develop the two systems in an appropriate manner. In addition, indicators and performance measures of the interdependence of the two systems must be properly defined. Exploring of modeling systems suitable for approaches on the interdependence of the two systems has been the subject of numerous research papers in the recent literature.